Typical Covid-19 case with primary pneumomediastinum in a 37 year old male - Jafari, Ramezan (Radiol Case Rep, 2021)
We report the case of a 37-year-old man who was admitted to Baqiyatallah hospital in Tehran (Iran) for retrosternal pain, fever, fatigue, dyspnoea and severe non-productive cough. The patient was subsequently confirmed as positive for COVID-19 at real-time polymerase chain reaction (RT-PCR) test. Chest computed tomography (CT) revealed also the presence of pneumomediastinum. This case highlights the importance of chest CT imaging for COVID-19 pneumonia to detect co-existing conditions as pneumomediastinum.